DIETARY VALUE AND SAFETY OF CARROTS IN THE DIET FOOD - Войцеховский, Владимир (SWorldJournal, 2020)
In article a detailed analysis of the biochemical composition of fresh carrots are presented. Changes in valuable components of the biochemical composition of carrots after prolonged storage have been analyzed. after 180 days of storage reduced the solids